Barriers to transition in young adults with neurogenic bladder. Issue 4 (August 2016) - Grimsby, G.M.; Burgess, R.; Culver, S.; Schlomer, B.J.; Jacobs, M.A.
Summary: Introduction: 'Transition' not only involves finding an adult healthcare provider, but also includes the process of developing the patient's ability to care for him/herself. Recent literature states that 40% of young adults with special healthcare needs are receiving the tools needed for transition. Pediatric urologists treating patients with complex anomalies, such as spina bifida, often anticipate poor outcomes for patients who are ill equipped for transition to adult care. The goal of this study was to identify potential barriers for young adults with neurogenic bladder when transitioning to independent care. Study design: A prospective IRB-approved study was performed on all patients with neurogenic bladder referred to the transitional urology clinic. Reasons for missed appointments were tracked, and all patients were asked to complete the Transition Readiness Assessment Questionnaire (TRAQ) in private prior to an appointment. The TRAQ responses are scaled 1–5, with higher numbers corresponding to higher transition readiness of each individual skill. The mean score for each question was calculated across all patients, and the mean TRAQ score was calculated across all questions for each patient. To assess if certain subgroups were more prepared for transition, mean scores were compared between sexes, patients aged <19 and ≥19 years old, and between ambulatory and full-time wheelchair users with unpaired t -tests. Results: A total of 73% (58/79) of patients referred to the transitional clinic came to their appointment. The most common reason for missed clinic appointments was related to health insurance coverage (47%). A total of 42 patients completed the TRAQ at a mean age of 19.5 years old; 90% (38/42) had spina bifida. Females, ambulatory patients, and those ≥19 years old had higher overall mean TRAQ scores, but these differences were not statistically significant. The highest TRAQ scores were related to taking and ordering medications, utilization of medical supplies, communication with healthcare providers, and assisting with household duties. The majority of the patients indicated 'I am learning to do this'. The lowest scores were in response to questions about health insurance coverage, payments for medications or medical equipment, financial help, and utilization of community services. Most patients responded 'I do not know how but I want to learn'. Conclusions: Young adults with neurogenic bladder needed the most guidance during transition to independent care, with management of health insurance and finances. Based on these findings, dedicated social work and nurse visits have been included into the transition process.